HUBUNGAN NILAI TROMBOSIT, HEMATOKRIT, LEUKOSIT, DAN RASIO TROMBOSIT-HEMATOKRIT DENGAN DERAJAT KLINIS DEMAM BERDARAH DENGUE PADA ANAK DI RSUD EMBUNG FATIMAH KOTA BATAM PADA TAHUN 2022-2024 - Kasih Purwati; Indriasari; Nazwa Aurelia Bazla (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Dengue Hemorrhagic Fever (DHF) remains a significant health problem among children, with clinical severity that may progress rapidly. Severity grading is associated with plasma leakage, bleeding manifestations, and circulatory disturbances. Hematological parameters, including platelet count, hematocrit level, leukocyte count, and the platelet-hematocrit ratio, are commonly used to assess disease progression. This study aimed to evaluate the relationship between these parameters and the clinical severity of DHF in pediatric patients. Methods: An analytical observational study with a cross-sectional design was conducted using medical records of pediatric DHF patients from 2022-2024. Samples were selected through total sampling based on inclusion and exclusion criteria. Data were analyzed using univariate and bivariate statistical methods according to the classification of the World Health Organization. Results: Most patients presented with thrombocytopenia and elevated hematocrit levels. Platelet count, hematocrit level, Leukocyte and platelet-hematocrit ratio were significantly associated with clinical severity (p < 0.05). Lower platelet-hematocrit ratios were observed in more severe cases. Conclusion: Platelet count, hematocrit level, and platelet-hematocrit ratio are significantly associated with the clinical severity of DHF in children and may serve as supportive indicators for assessing disease progression. Keywords: Dengue Hemorrhagic Fever, Platelet, Hematocrit, Leukocyte, Platelet-Hematocrit Ratio, Clinical Severity, Children